Internally Displacement and Cognitive Reasoning in Children of North Central, Nigeria - Agashua, Philemon Atume; Grace, Awopetu Ronke; Ugese, Jonathan Iornenge (American International Journal of Social Science Research, 2018)
The cognitive progression of displaced children has suffered major setback in Nigeria in recent time as a result of boko haram insurgency, Fulani herdsmen militia and communal clashes. Therefore, this study examines the cognitive reasoning of the children of primary and secondary school ages that are currently seeking refuge at internally displaced camps in North-Central, Nigeria. 1,222 internally displaced children were assessed using visual, numerical and verbal reasoning analysis tests respectively, developed by Barrett (2004). Of the total number of participants, 29.8% responded correctly to numerical reasoning tests, 15.6% answered correctly the verbal reasoning tests and 31.7% responded to visual analysis tests. The result showed that majority of the children could not respond correctly to reasoning and analysis tests.  The study concludes that children are worst vulnerable to current ongoing displacement in the country and this has resulted into downfall in the educational system and cognitive improvement of the children. It is therefore recommended that quick response to IDP children in the area of education should not be ignored or neglected in case of displacement of any type by government, philanthropists and non-governmental organizations.